A phase 1 randomized placebo-controlled safety and pharmacokinetic trial of a tenofovir disoproxil fumarate vaginal ring. (13th March 2016) - Keller, Marla J.; Mesquita, Pedro M.; Marzinke, Mark A.; Teller, Ryan; Espinoza, Lilia; Atrio, Jessica M.; Lo, Yungtai; Frank, Bruce; Srinivasan, Sujatha; Fredricks, David N.; Rabe, Lorna; Anderson, Peter L.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Tenofovir disoproxil fumarate (TDF), a prodrug of tenofovir (TFV), may be ideal for topical HIV preexposure prophylaxis because it has higher tissue and cell permeability than TFV; is not adversely impacted by seminal proteins; and its active metabolite, TFV-diphosphate (TFV-DP), has a long intracellular half-life. We engineered a TDF eluting polyurethane reservoir intravaginal ring (IVR) to provide near constant mucosal antiretroviral concentrations. Methods: A first-in-human randomized placebo-controlled trial was conducted to assess the safety and pharmacokinetics of the TDF IVR in healthy, sexually abstinent women (15 TDF and 15 placebo). Drug concentrations were measured in cervicovaginal fluid (CVF) obtained by swab, cervical tissue, plasma, and dried blood spots (DBS) over 14 days of continuous ring use. Results: There were 43 total, 23 reproductive tract, and eight product-related grade 1 adverse events. Steady-state CVF TFV concentrations were achieved proximal (vagina, ectocervix) and distal (introitus) to the TDF IVR 1 day after ring insertion. Median tissue TFV-DP concentrations 14 days after TDF IVR placement were 120 fmol/mg (interquartile range 90, 550). CVF collected from the cervix 1 week and 2 weeks after TDF IVR insertion provided significant protection against ex-vivo HIV challenge. Eleven of 14 (78%) participants had detectable TFV-DP DBS concentrations 14 days after TDF IVR placement, suggesting that DBS may provide a surrogate marker of adherence in future clinical trials. Conclusion: A TDF IVR is safe, well tolerated, and results in mucosal TFV concentrations that exceed those associated with HIV protection. The findings support further clinical evaluation of this TDF IVR.